(untitled) (INNOVATIVE ECONOMY, 2024)
Du W., Lishchynskyy I.O. CHINA’S AGRICULTURAL FOREIGN TRADE FLOWS: TRENDS, CHALLENGES, AND OPPORTUNITIES Purpose. The aim of the article is to analyse China’s agricultural import and export in the context of global geopolitical transformations and identification of trends, challenges, and opportunities for the state’s agricultural policy based on this analysis. Methodology of research. The following methods were used in the research: analysis and synthesis to evaluate the dynamics, product, and geographical structure of China’s agricultural foreign trade; SWOT analysis to assess the strengths, weaknesses, threats, and opportunities of the state’s agricultural policy; abstract and logical method to summarize information from various sources and create a comprehensive understanding of the researched problem, forming theoretical conclusions and generalizations; and graphical method to visualize the research results. Findings. It was found that in 2023, the dynamics of China’s foreign trade in agricultural products continued to show a growth trend that has been observed over the past decade. It was demonstrated that the development of China’s agricultural exports has effectively contributed to the deep expansion and diversification of the agricultural value chain, opening new opportunities for promoting high-quality agricultural development. At the same time, it was noted that China has abolished non-tariff measures on agricultural products and export subsidies for all agricultural products, making it one of the most open markets for agricultural products. However, it was proven that in terms of imports, China remains one of the most dependent countries in the world, which is related to the relatively small area of arable land, large population, and insufficient intensification, technological development, and mechanization of tangible agricultural production. Originality. The research on trends in the development of China’s international trade in agricultural products in the post-COVID period has been further developed, taking into account new geopolitical realities. Using the SWOT analysis method, the strengths, weaknesses, threats, and opportunities of China’s agricultural policy were identified. Practical value. The substantiated conclusions and recommendations derived from the research can be used to determine the strategic directions for the development of China’s trade relations, as well as to intensify agricultural trade flows between Ukraine and China. Key words: international trade, export, import, agriculture, peripheral regions, foreign policy, global risks, competitiveness.